Australia`s gold medal race from Montreal 1976 to Rio de Janeiro 2016 - Westerbeek, H.; Brockett, C.; de Bosscher, V.; Shibli, S.; van Bottenburg, M. (2013)
Conclusions A long history of increasing elite success - 30 years of elite sport system building A lot of very good and hard work that has led to success A national government system that increasingly is becoming a burden to system development A national approach (AIS) that led to regional expansion then regional kingdoms - then regional duplication Lack of a genuine national approach is starting to become a real problem - the next step towards maturation of the system A well developed system with a lot of good components to it that is now in transition - some parts move faster than other